Revisita del problema argentino de la lengua. Amado Alonso y la historia de una reescritura - Toscano y García, Guillermo (2022)
This paper addresses «El problema argentino de la lengua», an article published by Amado Alonso in 1932. To this end, we first analyze the type of theoretical and critical intervention that the author carries out; then, we consider it within a broader textual series that comprises a set of texts published between 1927, as Alonso becomes chair of the Institute of Philology of the University of Buenos Aires, and 1935, when he publishes the book El problema de la lengua en America, which includes a highly modified version of his 1932 work. We conclude that this article is an exceptional text in Alonso’s linguistic production as a whole, and that this exceptionality can be interpreted as a sign of the process of theoretical reformulation that he underwent during the period.